2017
DOI: 10.1002/bies.201700082
|View full text |Cite
|
Sign up to set email alerts
|

PTEN in the maintenance of genome integrity: From DNA replication to chromosome segregation

Abstract: Summary Faithful DNA replication and accurate chromosome segregation are the key machineries of genetic transmission. Disruption of these processes represents a hallmark of cancer and often results from loss of tumor suppressors. PTEN is an important tumor suppressor frequently mutated or deleted in human cancer. Loss of PTEN has been associated with aneuploidy and poor prognosis in cancer patients. In mice, Pten deletion or mutation drives genomic instability and development of various tumors with high penetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 49 publications
2
49
0
Order By: Relevance
“…The DLG2 GSEA of the NB datasets showed enrichment for Falconi anemia pathway, this is a DNA repair pathway (Tables 1 and 2), the functional loss of which is known result in an increased number of chromosomal breaks. DNA integrity is also one of the key functions of the G2/M checkpoint (32) and is lost if cells rapidly or abruptly leave the S phase. We have shown that DLG2 can regulate the cell cycle, namely by slowing the progression of cells through the G2/M checkpoint (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The DLG2 GSEA of the NB datasets showed enrichment for Falconi anemia pathway, this is a DNA repair pathway (Tables 1 and 2), the functional loss of which is known result in an increased number of chromosomal breaks. DNA integrity is also one of the key functions of the G2/M checkpoint (32) and is lost if cells rapidly or abruptly leave the S phase. We have shown that DLG2 can regulate the cell cycle, namely by slowing the progression of cells through the G2/M checkpoint (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…More recent evidence has shown that PTEN has phosphatase-independent roles in the nucleus where it regulates DNA replication and repair, chromatin dynamics, chromosome stability, and many other biological processes (23,24). Ma et al recently demonstrated that the majority of nuclear PTEN is phosphorylated at tyrosine residue-240 (pY240-PTEN) and that this phosphorylation was essential for PTEN's ability to bind chromatin, recruit RAD51…”
Section: Nuclear Pten Contributes To Mln4924 Sensitivity Through Its mentioning
confidence: 99%
“…PTEN has been shown to be directly involved in DNA fork progression, protection, and processing, and these pathways were among the most significant that differentiated sensitive and resistant groups (23,24). We aimed to test whether enrichment in replication fork processing and protection associated gene sets could predict MLN4924 response.…”
Section: Low Enrichment In Dna Fork Replication Pathways Can Predict mentioning
confidence: 99%
“…PTEN loss has been extensively linked to CIN, a biological role that is largely dependent on the scaffolding rather than the phosphatase function of PTEN [81], and therefore mostly independent of PI3K/Akt activity. Given that these PTEN effects can therefore not be modulated by pharmacological intervention targeting PI3K, these will therefore not be described here.…”
Section: Ptenmentioning
confidence: 99%
“…For an excellent review on the functions of PTEN in the maintenance of genome integrity, the reader is referred to Ref. [81].…”
Section: Ptenmentioning
confidence: 99%